Effects of biological soil crusts on bacterial diversity and soil properties in a Wisconsin sand prairie - Harried, Brittany (My University, 2017)
Sand prairies are a unique variant of the North American tallgrass prairie, found on sandy glacial and riverine deposits in the Upper Mississippi River (UMR) floodplain and elsewhere in the upper Midwest. Biological soil crusts (BSC) -- communities of bacteria, microalgae, fungi, archaea, and mosses, living within the top 3-14 mm of the soil -- provide important ecosystem services in sandy habitats worldwide. However, little is known about BSCs in Midwestern sand prairies. To characterize BSCs on a sand prairie in Wisconsin and quantify their effects on soil properties, soil samples were collected as matched pairs from disturbed, open sand areas (uncrusted) and nearby recovering BSC (crusted). Samples were analyzed for bacterial diversity and physical and chemical properties. Crusted samples contained significantly higher alpha and beta diversity. Proportions of major phyla, Cyanobacteria, Actinobacteria, Acidobacteria, and Bacteriodetes, were similar between crusted and uncrusted soils, but there was greater variation at the class and ordinal levels. Crusted soils had significantly higher organic material, total nitrogen, and total organic carbon, and were more resistant to erosion. These results indicate positive effects of BSCs on sand prairie habitat. These effects could be useful in restoration of sand prairie within the UMR floodplain and other sand prairie areas.
Keywords: Soils; Bacteria; Prairies--Wisconsin